Three doses of COVID-19 mRNA vaccine induce class-switched antibody responses in inflammatory arthritis patients on immunomodulatory therapies - Lee, Jenny M.; Figueroa, Alexis; Sachithanandham, Jaiprasath; Li, Maggie; Connolly, Caoilfhionn M.; Shapiro, Janna R.; Chen, Yiqun; Jones, Michelle; Dhara, Venkata Gayatri; Towns, Marilyn; Lee, John S.; Peralta, Stephanie R.; et al. (Frontiers in Immunology, 2023)
Patients with inflammatory arthritis (IA) are at increased risk of severe COVID-19 due to medication-induced immunosuppression that impairs host defenses. The aim of this study was to assess antibody and B cell responses to COVID-19 mRNA vaccination in IA patients receiving immunomodulatory therapies. Adults with IA were enrolled through the Johns Hopkins Arthritis Center and compared with healthy controls (HC). Paired plasma and peripheral blood mononuclear cell (PBMC) samples were collected prior to and 30 days or 6 months following the first two doses of mRNA vaccines (D2; HC=11 and IA=31 patients), or 30 days following a third dose of mRNA vaccines (D3; HC=11 and IA=96 patients). Neutralizing antibody titers, total binding antibody titers, and B cell responses to vaccine and Omicron variants were analyzed. Anti-Spike (S) IgG and S-specific B cells developed appropriately in most IA patients following D3, with reduced responses to Omicron variants, and negligible effects of medication type or drug withholding. Neutralizing antibody responses were lower compared to healthy controls after both D2 and D3, with a small number of individuals demonstrating persistently undetectable neutralizing antibody levels. Overall, most IA patients responded as well to mRNA COVID-19 vaccines as immunocompetent individuals by the third dose, with no evidence of improved responses following medication withholding. These data suggest that IA-associated immune impairment may not hinder immunity to COVID-19 mRNA vaccines in most individuals.